PEMBERDAYAAN KELOMPOK TERNAK DALAM PEMBUATAN PRODUK PENGENDALIAN LALAT RUMAH DENGAN TEKNIK ISOLASI (Z)-9-TRICOSENE SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT DI DESA MEURANDEH - Kartika Aprilia Putri; Beni Al Fajar; Hasby Hasby (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Today many farms have to be closed due to a large amount of air pollution (odor) and house fly attacks (Musca domestica), which fly in residential areas. There have been many attempts by the breeder to overcome the house fly attack, one of which is by giving insecticides. However, the use of pesticides that are not following the principle of integrated pest control. The purpose of this activity is to provide training the manufacture of home fly control products with isolation techniques (z)-9-tricosene as an effort to improve the economy of the society's economy in  meurandeh village. The method used in this activity is the method of approach directly, lectures, and practices. The way of procedure is carried out by listing the problems faced by society, especially a group of cattle Suka jadi and a group of cattle Mekar Jaya about the pest problem house flies and the marketing of products resulting from training activities. The lecture method carries out by providing information to the public about the advantages and benefits of trapping products and house fly traps as controlling population fluctuations of the pest house flies. The practical method carries out by providing extraction technique training (Z)-9-tricosene, which acts as a pheromone compound attracting male house flies.